Fruit, vegetables, and mushrooms for the preparation of extracts with α-amylase and α-glucosidase inhibition properties: A review. (15th February 2021) - Papoutsis, Konstantinos; Zhang, Jinyuan; Bowyer, Michael C.; Brunton, Nigel; Gibney, Eileen R.; Lyng, James
Highlights: The source of α-glucosidase has an impact on the experimental results. Diacylated anthocyanins have α-glucosidase and α-amylase inhibition activities. The activity of flavonoids is affected by subtle changes of their structure. The mechanism of action of fatty acids needs to be elucidated. Abstract: The inhibition of the α-amylase and α-glucosidase activity facilitates the maintenance of circulating glucose levels by decreasing the rate of blood sugar absorption. Existing enzyme inhibitors such as acarbose, miglitol, and voglibose are used for inhibiting the activity of these enzymes, however, alternative solutions are required to avoid the side-effects of using these drugs. The current study aims to review recent evidence regarding the in vitro α-amylase and α-glucosidase inhibition activities of extracts derived from selected fruit, vegetables, and mushrooms. The mechanisms of action of the extracts involved in the inhibition of both enzymes are also presented and discussed. Compounds including flavonoids, phenolic acids, anthocyanins, saponins, carotenoids, terpenes, sugars, proteins, capsaicinoids, fatty acids, alkaloids have been shown to have α-amylase and α-glucosidase inhibition activities. Harvesting period, maturity stage, sample preparation, extraction technique, and solvent type are parameters that affect the α-amylase and α-glucosidase inhibition activities of the extracts.